A study of building alteration towards building performance / Nurul Ashikin Razali - Razali, Nurul Ashikin (Faculty of Architecture, Planning and Surveying, 2013)
Building alteration has grown rapidly and the process involves human activities. Generally knew that building alteration is one of the needs of the occupants who do not comfort with their existing house. Alteration of house is a solution to fulfill their comfortable and desire. This dissertation is covering the definition of the study of building alteration, and the effect on the performance of building after carried out the alteration work. The selected case study use for the research is three areas residential which are Kampung Kubang Parit, Kampung Batin and Kuala Ibai. The party who also involves in this research is Majlis Bandaraya Kuala Terengganu (MBKT). There are several objectives that were achieved to ensure this research is successful. The objectives are to study the concept of building alteration, to study how the alteration can affect the performance of building and to define the awareness among the occupants about the requirement of the building approval to carry out alteration. In addition, the information was gathered by interview, observation, questionnaire, books, journals, internets and other related on it. There will be recommendation regarding the issues that arises related to the alteration works. So, at the end of this research it will meet the three of the objectives of this research. It can be conclude that the building alteration cannot give a guarantee towards performance of building in terms of comfort, safety and security to occupants. From this study, the author hopes that it will give the clear information to the readers and can be as reference in the future.